The development of the Malaysian competencies profile for the records manager / Mohamad Noorman Masrek, Rusnah Johare and Asmadi Mohammed Ghazali - Masrek, Mohamad Noorman; Johare, Rusnah; Mohammed Ghazali, Asmadi (Research Management Institute (RMI), 2011)
This study was undertaken with the aim to explore the competency profile of the records manager in Malaysian federal ministries. Problem statements, identified from review, include: (a) the advancement of Information & Communication Technology, (b) incompetent records managers, and (c) unavailability of Malaysian records manager competency profiles. Knowledge, skills and attitudes define competence. As the exploratory sequential approach concerns research methodology, the first phase of data collection involves contents analysis technique and on-line focus group discussions. Four competencies manual from United Kingdom, United States, Canada and Australia; and qualitative data from on-line focus groups discussions were transcribed and categorized to identify themes and patterns by applying manifest and latent coding. In the second phase, the data collected from a forementioned methods has been used to develop a survey questionnaire which drew the response of 182 Departmental Records Officer from 25 federal ministries. The mean ranking and descriptive statistics were used to analyze quantitative data. As for content analysis, two approaches have been used: quantitative and qualitative content analysis. Quantitative content analysis is concerned with assigning unit into appropriate categories and providing counts for each category, while qualitative content analysis comprises the relationship and connection between concepts. In quantitative content analysis, the frequency of reference made to the 106 sub-themes analyzed on the four manuals, indicates some variation. 42 sub-themes were identified to be refereed to in only one manual, 43 sub-themes in two manuals and 13 sub-themes in three manuals. Even so, similarities were found in the 106 referred sub-themes, which were used in all the manuals. In qualitative approach, the Australian Manual was found dominant in providing guidance and information in technical competencies such as records control, creation, disposition, maintenance, outsourcing, protection and IT capabilities. In contrast, the Canadian Manual was found to be outstanding in focusing on general competencies such as business management skills as well as interpersonal and personal skills, whereas the United States Manual was found to be the most frequently referred guide used in discussing records management. Findings from online focus group discussions (web blog) through the manifest approach revealed ten main themes and 39 sub-themes as follows: (a) competencies, (b) principles of records management, (c) problems in managing records, (d) training and education, (e) records management practices, (f) departmental records officers, (g) archives officers, (h) heads of departments, (i) the National Archives of Malaysia, and (j) electronic records.